Transformasi Spasial Hunian Pada Eks-Backpacker Enclaves Studi Kasus: Jalan Jaksa, Jakarta Pusat - Vika Haristianti; Wiwik Dwi Pratiwi (RUAS (Review of Urbanism and Architectural Studies), 2020)
This study aims to discover the extent of spatial transformation in residential areas on Jalan Jaksa, known as the ex-backpacker enclaves due to the concept of supply and demand. Spatial function, building facades, and corridors in residentials are the assessed variables. This study uses a qualitative method. Data collection is done by field observations, interviews, and literature review. The sampling method is using a non-random type or probability sample. The results of the analysis showed that from 26 samples there were 12 building/ residential samples (46.1%) that underwent installation, meaning that the building characteristics were adaptive, five buildings/ residential samples (19.2%) had insertion, meaning that the building was considered to be quite adaptive, and nine buildings/ residential samples (34 %) experiencing intervention, which means the building is not adaptive. In addition, the most changing category is the transformation in housing into multi-story buildings, lodging, and mixed-use buildings.